(untitled) (Kronika Bydgoska, 2020)
Deutsche Gesellschaft für Kunst und Wissenschaft in Bromberg was a society established in 1902 for coordination of all German activities in the field of culture and science, which was supposed to provide to the German community in the 19th-century Bydgoszcz an access to high culture. It had successfully continued its activity under the changed political conditions following the return of Bydgoszcz to the Homeland after 1920. Despite restrictions related to the drastically decreas- ing number of members, potential recipients and financial problems, the society - particularly in the 1920s - was not only very active, working as an organizer of cultural activities for the German minority, but also hosted events meeting the highest artistic and organizational standards. In the first years after the war, the Germans continued to be local leaders of cultural activities taking place in Bydgoszcz. This article shows activities organized by the society, showing the character, diversity, frequency and range of cultural events, as well as the role played by the German community in the cultural life of the interwar Bydgoszcz.